Paradigmas da docência na educação superior: da racionalidade técnico-instrumental ao paradigma crítico-reflexivo - Rosa, Francieli Nunes da (2014)
The present qualitative dissertation sought to understand teaching in higher education from two paradigms entitled: technical-instrumental rationality and critical-reflexive. The objective was to analyze and identify the way academic production in higher education has positioned itself in relation to the two paradigms between the years 1996 and 2014. Thus, the guiding question of the dissertation was: which of the two paradigms under discussion, the been more relevant in academic writing? The concern for the investigation of this theme was shown from discussions oriented in the research group titled Teacher Improvisation in the scenario of the expansion of higher education: the problem of the identity of the university professor. Thus, the research is classified as theoretical / bibliographical, associated to a documentary research. The theoretical reference for the first three chapters was constructed based on some specific bibliographies of the area, having as base authors: Alarcão (1996); Behrems (1998); Benincá (2002); Chauí (2001); Cunha (1998); Descartes (1993); Dewey (1979); Favero & Tonieto (2010); Freire (1983); Giroux (1996); Ghedin (2005); Kuhn (1991); Libane (1990); Masetto (1998); Mizukami (1986); Pérez Gómes (1995); Pimenta (2008); Rodrigues (2007); Rorty (1992); Sacristan (2000); Santos (2002); Silva Júnior (1996); Shön (2000); Skinner (1972); and Tardif (2009), who subsidized the exploration of concepts such as teaching in higher education, the expansion and democratization of teaching, teacher and student relationship, classroom research as construction of learning processes, education in technical perspective, teaching allied to the reflexive movement and the very formation of the university professor. The documentary research was constituted in the analysis of some periodicals on education, more precisely used in the last chapter. The choice of journals was free, the only criterion we used was to have articles published about teaching in higher education. The periodicals were: Educação UNISINOS (2014); Perspectiva UFSC (2011); Paidéia USP (1996); UNB Critical Lines (2008); Education and Reality UFRGS (2001); Education and Research USP (2013). This research comprised the investigation, examination and organization of the information that was categorized and analyzed for finally in this last chapter, we elaborated the bibliographic revision anchored in the authors Santos (2004), Buarque (2005) and Chauí (2003) for the proposed objective of the dissertation.